The Effect of Money Shocks on Interest Rates in the Presence of Conditional Heteroskedasticity. - Grier, Kevin B; Perry, Mark J (Journal of Finance, 1993)
Most current empirical work finds no evidence that money shocks lower interest rates. The authors show that these nonresults are mainly due to a failure to model the conditional heteroskedasticity of interest rates. Autoregressive conditional heteroskedasiticity (ARCH) models find a significant liquidity effect where ordinary least squares (OLS) models do not. The existence of a liquidity effect is found using different models and sample periods when ARCH models are used in estimation but never when OLS is employed.